Developing Low-Calorie Marshmallow Products Using Polyols and Soluble Fibers as Substitutes for Mono- and Disaccharides - Palabiyik, Ibrahim; Albas, Merve Gozde; Ersahin, Elif; Toker, Omer Said; Konar, Nevzat; Senturk, Bulent; Mutlu Abay, Nesrin; Kilavuz, Zuhal; Gok, Sila Barut; Tayyem, Reema; Karahan, Davut (AMER CHEMICAL SOC, 2025)
Marshmallow ingredient optimization is of critical importance in confectionery technology because even a slight change in its ingredients will prevent the formation of a foamy product structure. The aim of the study was to develop a low-calorie marshmallow by substituting corn syrup and mono- and disaccharides with soluble wheat fiber, inulin, and sugar alcohols. To this aim, the effects of variables on rheological and physical properties and general acceptability were investigated. Density values of marshmallows were determined between 0.33 and 1.30 g/cm3. General acceptability and density were chosen as the optimization parameters. General acceptability was maximum and density was minimum in the samples containing inulin, erythritol, maltitol syrup (MS), maltitol, and soluble wheat fiber at 15, 9.18, 39.19, 14.71, and 4.92%, respectively. The hardness, springiness, cohesiveness, gumminess, chewiness, and resilience of the marshmallow samples varied between 1544 and 3115 g, 0.369-0.532 and 0.369-0.532, 891-2632 g, 432-1356 g, and 0.190-0.513, respectively. The water activity of the optimized formulation (OM) was detected as 0.75 +/- 0.01. In this study, a sugar-free marshmallow formulation with the best product quality was successfully determined.
Keywords: SUGAR; GELATIN; TEXTURE; CONFECTIONERY; ISOMALTULOSE; QUALITY; STARCH; FOOD; Chemistry